2018
DOI: 10.1002/mrm.27352
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular stent artifacts in 3D‐TOF and 3D‐PCMRI: Influence of stent design on flow measurement

Abstract: The present results motivate the conception of low inductance or nonconductive stent design. Furthermore, the feasibility of near-stent 3D-PCMRI measurements opens the door to clinical applications like the post-treatment follow-up of stenoses or intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…We excluded patients with aneurysms presenting more than half of their volume with unreliable velocities with Vel an , 7.7 cm/s before FDS implantation. This threshold corresponds to the measurement error previously identified and reported in Pereira et al 22 and Bouillot et al 23 Flow Rates (QICA). As described in Bouillot et al, 24 measurement planes, each separated by 2 mm, were automatically placed orthogonal to the vessel center line within a user-selected distance corresponding to the C2-3 segment ( Fig 1C.1).…”
Section: Proportional Velocity-reduction Ratio Calculationsupporting
confidence: 58%
See 3 more Smart Citations
“…We excluded patients with aneurysms presenting more than half of their volume with unreliable velocities with Vel an , 7.7 cm/s before FDS implantation. This threshold corresponds to the measurement error previously identified and reported in Pereira et al 22 and Bouillot et al 23 Flow Rates (QICA). As described in Bouillot et al, 24 measurement planes, each separated by 2 mm, were automatically placed orthogonal to the vessel center line within a user-selected distance corresponding to the C2-3 segment ( Fig 1C.1).…”
Section: Proportional Velocity-reduction Ratio Calculationsupporting
confidence: 58%
“…This study was made possible due to prior investigations on intracranial stent-related artifacts. 23 In particular, we showed that these artifacts were mainly related to the shielding effect and were therefore restricted to the stent lumen. Furthermore, the following recent technical developments 24 were assembled in a postprocessing pipeline to obtain consistent and reliable PVRR and Vel an assessment from 4D-PCMR data: 1) the combination of 4D-PCMR data with 3DRA geometry for a precise delineation of the circulating domain; 2) the partial volume correction allowing unbiased ICA mean flow-rate quantification; and 3) the semiautomatic aneurysm extraction, thus ensuring a systematic and user-independent selection of the volume of interest and the consistent inclusion of the relevant aneurysm inflow velocities close to the neck.…”
Section: Pcmr Measurements and Flow Diversionmentioning
confidence: 77%
See 2 more Smart Citations
“…Earlier reports show that the number of wires in braided stents and stent design can affect the shielding effectiveness. 13 Other reports show that the shielding effects varied with stent materials, geometry, and orientation. Kalamazoo, MI, USA]) for the purpose of investigation of the relationship between RF-shielding effect and material and design.…”
Section: Discussionmentioning
confidence: 98%